PENGARUH KONDISI SIMPAN TERHADAP VIABILITAS DAN VIGOR BENIH Avicennia marina (Forsk.)Vierh. PADA BEBERAPA PERIODE SIMPAN - Halimursyadah Halimursyadah (Universitas Lampung, 2012)
The objective of the research was to determine the optimum storage condition (temperature and relative humidity) during 10 weeks with interval 2 weeks to maintain the seed viability and vigor. The variables were seed moisture content, gemination percentage, speed of germination, index of vigor, time to reach 50% germination, and electrolyte leachates. The research used split plot experi-mental design, with storage condition (AC and room temperature) as the main plot and storage period (0, 2, 4, 6, 8, and 10 weeks) as the subplot. The results showed seed stored at 90% relative humidity (using saturated KCl) and 19-200C temperature for 2 weeks storage periods significantly decrease in germination percentage (66.67%), speed of germination (64.56%), index of vigor (40.00%) and increased in time to reach 50% ger-mination (12.25 days) compared to the control, with germination percentage (94.67%), speed of germination (91.97%), index of vigor (49.33%), and time to reach 50% germination (11.25 days). Seed stored at 90% rela-tive humidity (using saturated KCl) and 27-280C temperature for 2 weeks storage periods showed significant decrease in germination percentage (36.00%), speed of germination (33.21%), index of vigor (21.33%), and increase in time to reach 50% germination (13.41 days) and electrolyte leachates (42.99 μScm-1g-1) as com-pared to untreated with 89.33% germination, 87.98% speed of germination, 49.33% index vigor, time to reach 50% germination (11.75 days), and electrolyte leachates (36.16 μScm-1g-1). Storage condition using saturated NaCl at 19-200C (AC) or 27-280C (ambient) with 80% RH and 75% RH, respectively, showed decrease in ger-mination compared to using saturated KCl at the same storage temperature. At 4 and 6 weeks storage periods at AC or ambient temperature showed declining in viability and vigor. Total loss of viability and vigor occured at 8 and 10 weeks storage. The seeds can be stored at 90% RH (using saturated KCl) and low temperature (AC) for up to 2 weeks; after that period, viability and vigor declined. Key words: storage condition, strorage period, seed viability, and vigor